Identifikasi Waste dengan Menggunakan Value Stream Mapping di Gudang PT. XYZ - Prayogo, Thomas; Octavia, Tanti (Jurnal Titra, 2013)
PT. XYZ is one of the leading cigarette manufacturers in Indonesia. It has four type of warehouses there is spare part, DIM, clove and leaf. The company is continuously improving and increasing its working quality by examining the waste. The Value Stream Mapping is the concept in the Lean Manufacturing to examine the waste. Two number of waste are identified inside the spare part warehouse. They are transportation and waiting waste. From the waste analysis, the transportation waste could be reduced to 39.98%, 49.71%, 100% and waiting waste could be reduce to 70,34%. Transportation and waiting waste are also identified inside the DIM warehouse. From the waste analysis, they could be reduced to 50.05% and 100%. There is only one waste identified in the clove and leaf warehouse, there is over processing and inventory, respectively. From the waste analysis, the waste could be reduced as much as 50.5% and 100% respectively.